Package set-def: set-def
Information
name | set-def |
version | 1.14 |
description | set-def |
author | Joe Hurd <joe@gilith.com> |
license | HOLLight |
provenance | HOL Light theory extracted on 2011-09-21 |
show | Data.Bool Set |
Files
- Package tarball set-def-1.14.tgz
- Theory file set-def.thy (included in the package tarball)
Defined Type Operator
- Set
- set
Defined Constants
- Set
- ∅
- bigIntersect
- bigUnion
- bijections
- choice
- cross
- delete
- \
- disjoint
- fromPredicate
- image
- injections
- insert
- ∩
- ∈
- ⊂
- rest
- singleton
- ⊆
- surjections
- ∪
- universe
Theorems
⊦ ∀s. rest s = delete s (choice s)
⊦ ∀p x. x ∈ fromPredicate p ⇔ p x
⊦ ∅ = { x. x | F }
⊦ universe = { x. x | T }
⊦ ∀s. ¬(s = ∅) ⇒ choice s ∈ s
⊦ ∀s. singleton s ⇔ ∃x. s = insert x ∅
⊦ ∀s t. disjoint s t ⇔ s ∩ t = ∅
⊦ ∀s t. bijections s t = injections s t ∩ surjections s t
⊦ ∀s t. s ⊂ t ⇔ s ⊆ t ∧ ¬(s = t)
⊦ ∀s t. s = t ⇔ ∀x. x ∈ s ⇔ x ∈ t
⊦ ∀s t. s ⊆ t ⇔ ∀x. x ∈ s ⇒ x ∈ t
⊦ ∀s t. (∀x. x ∈ s ⇔ x ∈ t) ⇒ s = t
⊦ ∀s. bigIntersect s = { x. x | ∀u. u ∈ s ⇒ x ∈ u }
⊦ ∀s. bigUnion s = { x. x | ∃u. u ∈ s ∧ x ∈ u }
⊦ ∀x s. insert x s = { y. y | y = x ∨ y ∈ s }
⊦ ∀s t. s ∩ t = { x. x | x ∈ s ∧ x ∈ t }
⊦ ∀s t. s ∪ t = { x. x | x ∈ s ∨ x ∈ t }
⊦ ∀s x. delete s x = { y. y | y ∈ s ∧ ¬(y = x) }
⊦ ∀s t. s \ t = { x. x | x ∈ s ∧ ¬(x ∈ t) }
⊦ ∀f s. image f s = { y. y | ∃x. x ∈ s ∧ y = f x }
⊦ ∀s t. cross s t = { x y. Data.Pair., x y | x ∈ s ∧ y ∈ t }
⊦ ∀s t.
surjections s t =
{ f. f | (∀x. x ∈ s ⇒ f x ∈ t) ∧ ∀x. x ∈ t ⇒ ∃y. y ∈ s ∧ f y = x }
⊦ ∀s t.
injections s t =
{ f. f |
(∀x. x ∈ s ⇒ f x ∈ t) ∧ ∀x y. x ∈ s ∧ y ∈ s ∧ f x = f y ⇒ x = y }
Input Type Operators
- →
- bool
- Data
- Pair
- Data.Pair.×
- Pair
Input Constants
- =
- select
- Data
- Bool
- ∀
- ∧
- ⇒
- ∃
- ∨
- ¬
- F
- T
- Pair
- Data.Pair.,
- Bool
Assumptions
⊦ T
⊦ (∃) = λP. P ((select) P)
⊦ ∀t. (∀x. t) ⇔ t
⊦ ∀t. (λx. t x) = t
⊦ (∀) = λp. p = λx. T
⊦ ∀x. x = x ⇔ T
⊦ (⇒) = λp q. p ∧ q ⇔ p
⊦ (∧) = λp q. (λf. f p q) = λf. f T T
⊦ ∀P. ¬(∀x. P x) ⇔ ∃x. ¬P x
⊦ (∃) = λP. ∀q. (∀x. P x ⇒ q) ⇒ q
⊦ ∀f g. f = g ⇔ ∀x. f x = g x
⊦ (∀t. ¬¬t ⇔ t) ∧ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀t. ((T ⇔ t) ⇔ t) ∧ ((t ⇔ T) ⇔ t) ∧ ((F ⇔ t) ⇔ ¬t) ∧ ((t ⇔ F) ⇔ ¬t)
⊦ ∀t. (T ∧ t ⇔ t) ∧ (t ∧ T ⇔ t) ∧ (F ∧ t ⇔ F) ∧ (t ∧ F ⇔ F) ∧ (t ∧ t ⇔ t)
⊦ ∀t. (T ⇒ t ⇔ t) ∧ (t ⇒ T ⇔ T) ∧ (F ⇒ t ⇔ T) ∧ (t ⇒ t ⇔ T) ∧ (t ⇒ F ⇔ ¬t)